TEACHER PERFORMANCE IS REVIEWED FROM INCENTIVES, ORGANIZATIONAL CULTURE, PROFESSIONAL COMPETENCE, INFRASTRUCTURE IN MTs NEGERI 8 SRAGEN - Evi Nurhayati; Istiatin Istiatin; Sudarwati Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The research on teacher performance in MTs Negeri 8 Sragen aims to research and test the influence of incentives, organizational culture, professional competence, and infrastructure on teacher performance in MTs Negeri 8 Sragen. The design of the research conducted is quantitative descriptive research. The research will be conducted at MTs Negeri 8 Sragen, located at Jl. Solo – Purwodadi KM. 13, Siboto Rt 11, Kalimacan, Kalijambe, Sragen. This study used the entire population so-called saturated sampling, in this study used all teachers as many as 34 teachers consisting of 17 civil servant teachers and 17 honorary teachers in MTs Negeri 8 Sragen as a research sample. The data analysis technique used in this study uses multiple linear regression analysis that has previously been performed instrument tests and classical assumption tests with SPSS 23 software. The conclusion obtained by this study is that there is a positive and significant influence of incentives, organizational culture, professional competence on teacher performance in MTs Negeri 8 Sragen. Incentive variables, organizational culture, professional competence and infrastructure contributed to teacher performance by 67.1%, while the remaining 32.9% was explained by other variables not proposed in the study. Keywords: incentives, organizational culture, teacher performance, professional competence and infrastructure